The specificity and catalytic properties of Alu I methylase - Han, Moon H. (2012)
The specific methylation site for Alu I methylase was the cytosine nucleotide in Alu I sequence. The position of the methylated cytosine nucleotide was determined by the chemical cleavage reactions of the Maxam-Gilbert DNA sequencing procedure. As expected, the methylated cytosine nucleotide bands were disappeared on C+ T and C lanes on 12% sequencing gels.